Relationship Between Adherence to Individual Goals Within the 5‐2‐1‐0 Guidelines for Obesity Prevention and Number of PACER Laps in Adolescents. (October 2017) - Cho, Kibum; Jones, Emily; Lilly, Christa; Bulger, Sean; Braga, Luciana; Elliott, Eloise
ABSTRACT: BACKGROUND: The purpose of this study was to evaluate the relationship between adolescents' adherence to the 5‐2‐1‐0 goals and the number of completed Progressive Cardiovascular Endurance Run (PACER) laps. METHODS: Participants included 1792 students aged 10 to 16 years who were randomly selected across 9 data collection periods between 2012 and 2014. The Survey of Physical Activity and Nutrition was used to measure time spent in physical activity and sedentary behavior, and dietary intake and the dependent variable was the number of PACER laps achieved. The Kruskal‐Wallis test and pairwise post hoc comparisons were conducted. RESULTS: Only 0.95% (N = 17) participants met all 4 goals outlined within the 5‐2‐1‐0 guidelines. Whereas 10.04% met 3 (N = 180), 41.63% met 2 (N = 746), 34.99% met 1 (N = 627), and 12.39% did not meet any goals (N = 222). Pairwise comparisons indicated there were significant differences: between groups not meeting any of the 5‐2‐1‐0 goals and other groups (meeting one goal [p = .000], 2 goals [p = .000], 3 goals [p = .000], and all 4 [p = .008]). CONCLUSIONS: The positive relationship between PACER laps and adherence to the 5‐2‐1‐0 goals suggests targeted and sequential behavioral changes may have positive implications on adolescents' cardiovascular fitness and body mass index.